LDL particle core enrichment in cholesteryl oleate increases proteoglycan binding and promotes atherosclerosis - Melchior, John T. (The American Society for Biochemistry and Molecular Biology, 2013)
Several studies in humans and animals suggest that LDL particle core enrichment in cholesteryl oleate (CO) is associated with increased atherosclerosis. Diet enrichment with MUFAs enhances LDL CO content. Steroyl O-acyltransferase 2 (SOAT2) is the enzyme that catalyzes the synthesis of much of the CO found in LDL, and gene deletion of SOAT2 minimizes CO in LDL and protects against atherosclerosis. The purpose of this study was to test the hypothesis that the increased atherosclerosis associated with LDL core enrichment in CO results from an increased affinity of the LDL particle for arterial proteoglycans. ApoB-100-only Ldlr(−/−) mice with and without Soat2 gene deletions were fed diets enriched in either cis-MUFA or n-3 PUFA, and LDL particles were isolated. LDL:proteogylcan binding was measured using surface plasmon resonance. Particles with higher CO content consistently bound with higher affinity to human biglycan and the amount of binding was shown to be proportional to the extent of atherosclerosis of the LDL donor mice. The data strongly support the thesis that atherosclerosis was induced through enhanced proteoglycan binding of LDL resulting from LDL core CO enrichment.